Youth spirituality - Resurreccion, Ron R. (Animo Repository, 2006)
The spirituality of the youth will be described in terms of their thoughts, feelings, and experiences about it. This study will utilize the focus group methodology in order to provide the researchers with unanti<;:ipated, in depth individual information as well as group perspectives. The focus group discussions will generate stories from the respondents as these relate to the questions posed by a moderator. . There will be four Focus Group Discussion (FGD) groups (two from an urban setting and two from rural) composed of 5 to 8 members ( c_ombination of males and females) per group. The discussion will last for I to 1.5 hours. Respondents aged 13 to 20 years shall be recruited from urban and rural high schools using purposive procedure. Informed consent will be provided. Grounded Theory will be used as basis for qualitative analysis. This will entail an inductive approach to coding data, wherein codes and categories are generated from the transcribed text.' Each FGD session will be transcribed verbatim. The senior researcher and the graduate. student assistant will independently code each transcript by hand, coding individual sentences and sentence fragments. Codes will be created, refined, or eliminated by establishing differences and similarities among fragments originally subsumed under each of the initial codes. Attempts to reconcile discrepancies will also be made by the research team. '